2023
DOI: 10.3390/curroncol30070487
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Cutaneous Squamous Cell Carcinoma of the Head and Neck: A Review

Abstract: Non-melanoma skin cancer of the head and neck (NMSCHN) is one of the most common malignancies worldwide, and its incidence is growing at a significant rate. It has been found to be aggressive in its spread and has the capacity to metastasize to regional lymph nodes. Cutaneous squamous cell carcinoma (cSCC) has a considerably high mortality rate. It has remarkable characteristics: diameter >2 cm, depth >5 mm, high recurrence, perineural invasion, and locoregional metastases. Aggressive cSCC lesions most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Cutaneous squamous cell carcinoma (cSCC) is the second most common malignancy in humans, after basal cell carcinoma, presenting with an annual incidence of 1.8 million in the US ( 1 , 2 ). The reported metastatic and mortality rate of cSCC varies at 2%–5% and 1%–2%, respectively ( 1 – 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous squamous cell carcinoma (cSCC) is the second most common malignancy in humans, after basal cell carcinoma, presenting with an annual incidence of 1.8 million in the US ( 1 , 2 ). The reported metastatic and mortality rate of cSCC varies at 2%–5% and 1%–2%, respectively ( 1 – 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, aggressive cSCC tumors are ulcerated, >2 cm, and often occur on the sun damaged skin of the head and neck of elderly Caucasian men. These tumors have a higher risk for metastasis, unfavorable response to standard treatments, and eventually end in mortality ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that predispose patients to develop cSCC include light skin, exposure to sunlight, ultraviolet radiation, immunosuppression, human papillomavirus, chronic conditions that lead to scarring, genetic syndromes, and certain environmental exposures [ 4 ]. The main high-risk prognostic markers for cSCC include the tumor size, site, history of radiotherapy, immunosuppression, and perineural invasion [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant histological variable is perineural invasion. Perineural invasion predicts a poor prognosis in several cancers such as pancreatic [ 37 ], gastric [ 38 ], and head and neck CSCC [ 39 ]. In the present study, it was found that patients with tumors presenting perineural invasion had a significantly higher risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%